Lurik Fabric Production in Klaten: Science Learning Resource in Elementary – Ethnoscience Perspective - Nisa, Khoirun; Sayekti, Ika Candra (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study is to analyze the ethnoscience elements in the Klaten Regency’s lurik fabric production process and to identify how these ethnoscience aspects can be used as a science learning resource in elementary schools. Methodology: This study used a qualitative approach with a phenomenological design and was conducted in Bendo and Beji villages in Pedan District, Klaten Regency. Data were collected through observation, open interviews, documentation, and a literature review related to Klaten’s lurik fabric, using technique and source triangulation to ensure data validity. The data analysis included data collection, data reduction, data presentation, and conclusion drawing. Results: The results showed that the lurik fabric production process consists of six main stages that can be integrated into elementary science learning. For grade 3, relevant topics include forms of energy, energy sources, and changes in the form of objects; for grade 4, plant organs, energy changes, and types of forces; for grade 5, heat transfer, simple machines, and magnetism; and for grade 6, the motion system. Beyond content integration, the lurik fabric ethnoscience can also develop students’ process skills such as observing, planning and conducting investigations, processing and analyzing data, as well as evaluating and reflecting. Furthermore, it can cultivate scientific attitudes like curiosity, discovery and creativity, accuracy, resilience in facing failure, and collaboration. Applications/Originality/Value: The application of this research is to provide an authentic, local-culture-based learning resource that enriches science education with contextual, meaningful experiences connected to students’ cultural heritage.